PERTANGGUNGJAWABAN PIDANA PERUSAKAN GEDUNG DAN FASILITAS RUTAN OLEH NARAPIDANA (Analisa Putusan Pengadilan Nomor 311/Pid.Sus/2019/PN. Sgi) - Siagian, Edumanihar; Suhaidi, Suhaidi; Affan, Ibnu (Jurnal Ilmiah METADATA, 2021)
The treatment of differences in State Detention Centers is still frequent, so that this can lead to jealousy among detainees. One form of crime or crime that occurs in State Detention Centers is the destruction of spaces / buildings and facilities by inmates. The formulation of the problem in this thesis is how the factors that cause the destruction of the building and facilities of the detention center by inmates, what is the criminal responsibility of prisoners who destroy buildings and detention facilities, how judges consider in verifying the crime of destroying detention buildings and facilities in the verdict. Court Number 311 / Pid.Sus / 2019 / PN Sgi. The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the factors that led to the destruction of the building and facilities of the detention center were dispenser problems in which the prisoners and prisoners were angry and objected because the dispensers that had previously been distributed and placed in the rooms of the prisoners had been taken back by the guards. / Rutan employees. The criminal responsibility for the convict who destroys the building and facilities of the detention center is that the defendant is sentenced to 9 (nine) months imprisonment. The judge's consideration in making a decision on the crime of destroying the buildings and facilities of the detention center in the Court Decision Number 311 / Pid.Sus / 2019 / PN Sgi is that the Panel of Judges has considerations starting from the demands of the Public Prosecutor, the fulfillment of the elements in accordance with the articles charged. and there are no justifying and forgiving reasons, so that they are found guilty, as well as burdensome and mitigating things.